A COMMUNITY BASED CROSS-SECTIONAL STUDY ON MORBIDITY PATTERN OF ELDERLY IN RURAL AREA OF JHALAWAR, RAJASTHAN - THAKAN, SOMYA; MEHTA, ADITYA; SINGH, RAGHAV (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to study the morbidity pattern and burden among the elderly residing in the field practice area of Rural Health Training Centre Mandawar. The aim of the study was to identify the various factors associated with morbidity among the study population. Assessment of the morbidity profile will help in the application of interventions, to improve the health status and the quality of life of the elderly. Methods: Therefore, a total of 880 elderly were selected. Multiple house visits were done and data were collected by interviewer method, observation, and clinical examination of the study population. Diagnosis of the disease was made on the basis of history, investigations, clinical examination, and treatment report. Statistical analysis was done using Statistical Package for the Social Sciences 25 trial version. Results: Out of 880 elderly, 83.9% belonged to the age group of 60–74 years, the majority (87.4%) were found to be Hindus, 44% lived in three generation families. The most of the elderly were illiterate (46.7%) and the majority (44.2%) belonged to class IV socio-economic status. The morbidity load was 2370. The average morbidity per person was 1.56. The majority of the elderly (32%) had two morbidities. Visual impairment was the most common morbidity and it was more common in males. The association of morbidity was found to be statistically significant with gender, age category, and financial status. Conclusion: The present study revealed that the prevalence of morbidity among the elderly is very high.